КОМПЛЕКС ВПРАВ З РОЗВИТКУ ПРОФЕСІЙНОЇ ПЛЮРИЛІНГВАЛЬНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ МЕНЕДЖЕРІВ ЗОВНІШНЬОЕКОНОМІЧНОЇ ДІЯЛЬНОСТІ - Піскурська, Ганна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглянуто питання розробки ефективного комплексу вправ для формування професійної плюрилінгвальної компетентності майбутніх менеджерів зовнішньоекономічної діяльності в умовах організованого навчання у вищій школі. Автором надано детальну характеристику системі спеціальних багатомовних лексичних, рецептивних, медіативних та інтерактивних вправ та наведено приклади кожного типу вправ. В статье рассмотрена проблема разработки эффективного комплекса упражнений для формирования профессиональной плюрилингвальной компетентности будущих менеджеров внешне-экономической деятельности в условиях организованного обучения в высшей школе. Автором предоставлена подробная характеристика системы специальных многоязычных лексических, рецептивных, медиативных и интерактивных упражнений и приведены примеры каждого типа упражнений. The article focuses on the problem of developing an effective set of tasks for the development of future International Business Managers’ professional plurilingual competence under conditions of organized training in the higher school. The special set of exercises is a series of multilingual tasks divided into sections according to a certain type of speech activity. The author provides a detailed characteristics of each type of lexical, receptive, meditative, and interactive tasks. Besides, the set of exercises is also divided into units according to the following professional topics: company structure; production and services; marketing; buying and selling; contracts and agreements; finance; business ethics. Such thematic and functional division of the set of exercises enhances students’ motivation towards language learning, contributes to the development of «code-switching» strategy, and eliminates psychological barriers while taking part in multilingual intercultural communication.